Changes in Hypertension Treatment in the Yaroslavl Region of Russia: Improvements Observed Between 2 Cross‐Sectional Surveys. Issue 12 (9th October 2013) - Mozheyko, Maria; Eregin, Sergey; Vigdorchik, Alexey; Tobe, Sheldon; Campbell, Norman; Riahi, Farhad; Hughes, David
<x xml:space="preserve">Abstract</x> This prospective before‐and‐after survey of hypertensive patients visiting government‐run outpatient health facilities in the Yaroslavl Region of Russia assessed blood pressure (BP)–related endpoints following initiation of a comprehensive health system improvement program for hypertension. Two cross‐sectional surveys, one at baseline and the other approximately 1 year after program initiation, evaluated the primary measure of BP control rate. Secondary measures included mean BP levels and distribution, cardiovascular risk factors, and associated conditions, heart rate levels, and antihypertensive therapy. From the 2011 survey (n=1794) to the 2012 survey (n=2992), BP control rate (<140/90 mm Hg) significantly increased from 16.8% to 23.0%, reflecting a 37% relative improvement (P<.0001). Mean BP level was significantly reduced from 151/90 mm Hg to 147/88 mm Hg (P<.0001). Severe uncontrolled hypertension (systolic BP ≥180 mm Hg) was reduced from 9.7% to 6.4% (P<.0001). Implementing a guidelines‐based treatment protocol with medical and patient education programs resulted in physician behavior change and improved patient BP control.